2017
DOI: 10.1590/2358-2936e2017029
|View full text |Cite
|
Sign up to set email alerts
|

An update for cladoceran fauna (Crustacea, Branchiopoda) from Lake Paranoá, Central Brazil, with the first description of a male of Leydigiopsis ornata Daday, 1905

Abstract: Until recently, Lake Paranoá was considered the most thoroughly studied aquatic environment in relation to cladocerans in the Federal District. However, in new samplings carried out during the dry and rainy seasons of 2014, we found 10 new records of species. Th ese species were presumed to occur in Lake Paranoá because of their range of geographical distribution. Th e male of Leydigiopsis ornata Daday, 1905 is described for the fi rst time, adding new morphological traits to a recent redescription of the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Toxins 2023, 15, x FOR PEER REVIEW 13 of 26 10 shows the relative abundance of these classes in each SSF at the end of the filtration run. Some of the classes identified on the SSFs, among others, have been previously recorded in the Paranoá Lake microbial community [56]. In addition, in previous studies, these same classes were also identified in the system of slow sand filtration using this lake water [45,47,57,58].…”
Section: Characterization Of the Microbiota In Slow Sand Filterssupporting
confidence: 62%
See 2 more Smart Citations
“…Toxins 2023, 15, x FOR PEER REVIEW 13 of 26 10 shows the relative abundance of these classes in each SSF at the end of the filtration run. Some of the classes identified on the SSFs, among others, have been previously recorded in the Paranoá Lake microbial community [56]. In addition, in previous studies, these same classes were also identified in the system of slow sand filtration using this lake water [45,47,57,58].…”
Section: Characterization Of the Microbiota In Slow Sand Filterssupporting
confidence: 62%
“…Species of the genus Arcella are often found in sediments or decomposing vegetation, where they feed on bacteria, algae, and organic debris. Species Some of the classes identified on the SSFs, among others, have been previously recorded in the Paranoá Lake microbial community [56]. In addition, in previous studies, these same classes were also identified in the system of slow sand filtration using this lake water [45,47,57,58].…”
Section: Characterization Of the Microbiota In Slow Sand Filtersmentioning
confidence: 55%
See 1 more Smart Citation